2013
DOI: 10.1097/inf.0b013e31829bb0b9
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Diversity and Mixed Infection in Newborn Disease and Hearing Loss in Congenital Cytomegalovirus Infection

Abstract: Background Congenital cytomegalovirus (cCMV) is a common congenital infection and a leading non-genetic cause of sensorineural hearing loss (SNHL). CMV exhibits extensive genetic variability and infection with multiple CMV strains (mixed infection) was shown to be common in cCMV. The role of mixed infections in disease and outcome remains to be defined. Methods Genotyping of envelope glycoproteins, UL55 (gB), UL73 (gN) and UL75 (gH) was performed on saliva specimens from 79 infants from the ongoing CMV and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
47
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 34 publications
(49 reference statements)
6
47
0
Order By: Relevance
“…6,7 However, the claims are controversial. 8 In Cuba, a preceding study performed in Havana showed an intermediate rate (1.1%) of CMV congenital infection in newborns (NB) and a 92.7% of seroprevalence in pregnant women (PW). 9 However, the frequency of symptomatic CMV congenital infection across the country, and its association with gB genotype, viral load and clinical symptoms has never been studied.…”
Section: Introductionmentioning
confidence: 98%
“…6,7 However, the claims are controversial. 8 In Cuba, a preceding study performed in Havana showed an intermediate rate (1.1%) of CMV congenital infection in newborns (NB) and a 92.7% of seroprevalence in pregnant women (PW). 9 However, the frequency of symptomatic CMV congenital infection across the country, and its association with gB genotype, viral load and clinical symptoms has never been studied.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have found some evidence to correlate specific genotypes with disease outcome, investigating polymorphisms in the UL55 (glycoprotein B) (16)(17)(18)(19), UL73 (glycoprotein N) (20)(21)(22), UL75 (glycoprotein H) (23), UL144 (tumor necrosis factor alpha [TNF-␣]-like receptor) (24)(25)(26), and UL146 and UL147 (viral CXCL chemokines) (27,28) genes. Others, however, found no evidence of these relationships (29)(30)(31)(32). Overall, these studies have focused on one or, at best, a few genes at a time, ignoring the influence of other variable regions in the genome.…”
mentioning
confidence: 99%
“…The fetal brain and auditory system are the main sites of the clinical manifestations of congenital HCMV (cCMV) infection (1)(2)(3)(4), and sensorineural hearing loss is the most common long-term sequela in congenitally infected infants (4)(5)(6). In the fetal brain, the bilateral subventricular zone (SVZ), where neural progenitor/stem cells (NPCs) are a predominant cell type, is a site of virus-induced damage that has been well described in infants with severe congenital HCMV infection (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%